Mine! - Fleming, Candace; Rohmann, Eric (Anne Schwartz Books, 2023)
A group of forest animals vie for the same delicious red apple that is just about to drop.
Ages 3-7.
Grades K-1.
Keywords: Stories in rhyme; Animal fiction; Picture books